Plant and animal protein for muscle mass and strength gains: a systematic review - A. V. Meshtel; P. D. Rybakova; A. B. Miroshnikov; V. D. Vybornov; A. G. Antonov; R. A. Khanferyan; M. M. Korosteleva (National Electronic Information Consortium (NEICON), 2023)
Background: Controversial approaches to studying the effect of proteins of various origins on the functional parameters of human skeletal muscles have led to the erroneous opinion that plant-based protein is a lesser stimulator of muscle mass growth and muscle strength than animal protein. Therefore, the purpose of this systematic review was to actually evaluate the effects of plant and animal protein intake on muscle mass and strength through studies comparing protein supplements.Methods: Literature search was carried out in the databases PubMed, Research Gate and the database of the Russian State Library. Studies were considered both in English and in Russian, over the past 20 years, filtered by date: from July 2002 to July 2022. Inclusion Criteria: Participants are healthy men and women over 18 years of age; taking protein supplements from plant products (soy, wheat, pea, rice, etc.); comparison with a group taking protein supplements from animal products (whey, beef, egg, etc.); studies assessed lean and/or muscle mass and assessed participants' muscle strength before and after supplementation; randomized controlled trial.Results: A total of 970 studies were found. After initial screening for title and abstract, 938 studies were excluded. Of the 32 publications selected, 5 duplicates were excluded, and after a secondary selection, 18 studies that did not meet the PICOS criteria were excluded. As a result of the search and selection, the review included 9 publications.Conclusions: Athletes and active individuals who prefer to consume plant-based protein products may not be inferior in terms of muscle strength and muscle mass to those athletes who prefer animal-based protein products. To further explore this topic, more randomized controlled trials should be conducted, taking into account the requirements for standardization and with a large number of participants.Registration: PROSPERO 2022 CRD42022345245